Ferritin as an Effective Prognostic Factor and Potential Cancer Biomarker - Katarzyna Szymulewska-Konopko; Joanna Reszeć-Giełażyn; Monika Małeczek (Current Issues in Molecular Biology)
Ferritin is found in all cells of the body, serving as a reservoir of iron and protecting against damage to the molecules that make up cellular structures. It has emerged as a biomarker not only for iron-related disorders but also for inflammatory diseases and conditions in which inflammation plays a key role, including cancer, neurodegeneration, and infection. Oxidative stress, which can cause cellular damage, is induced by reactive oxygen species generated during the Fenton reaction, activating signaling pathways associated with tumor growth and proliferation. This review primarily emphasizes basic studies on the identification and function of ferritin, its essential role in iron metabolism, its involvement in inflammatory diseases, and its potential as an important prognostic factor and biomarker for cancer detection.